2015
DOI: 10.11604/pamj.2015.21.25.7022
|View full text |Cite
|
Sign up to set email alerts
|

Rétraction: plagiat aggravé dans l’article: aspergillose broncho-pulmonaire allergique lors d’un asthme réfractaire: à propos d’un cas clinique par Khalid Lahmadi et al (doi:10.11604/pamj.2015.20.350.6572)

Abstract: Cet article retracte l'article "Aspergillose broncho-pulmonaire allergique lors d'un asthme réfractaire: à propos d'un cas clinique. Khalid Lahmadi, Hind El Youssi, Jawad Rochdi, BoughrineNawal, Er-Rami Mohammed. The Pan African Medical Journal. 2015;20:350. (doi:10.11604/pamj.2015.20.350.6572)"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…To date there is no evidence that S. aureus can be a causative agent of acne vulgaris, but its role in acne formation is expected. In addition, we can mention that S. aureus colonizes many skin areas affected by psoriasis and atopic dermatitis (Elfatoiki et al, 2016; Lacey et al, 2016), and causes inflammation and treatment complications. Inside skin glands and hair follicles, the quite aerotolerant C. acnes prefers to colonize anaerobic micro-niches (Matard et al, 2013), where it forms complex biofilms that include S. aureus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there is no evidence that S. aureus can be a causative agent of acne vulgaris, but its role in acne formation is expected. In addition, we can mention that S. aureus colonizes many skin areas affected by psoriasis and atopic dermatitis (Elfatoiki et al, 2016; Lacey et al, 2016), and causes inflammation and treatment complications. Inside skin glands and hair follicles, the quite aerotolerant C. acnes prefers to colonize anaerobic micro-niches (Matard et al, 2013), where it forms complex biofilms that include S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that colonization of acne lesions by S. aureus can strengthen inflammation (Totté et al, 2016; Dreno et al, 2017). Moreover, S. aureus can be responsible for complications and inflammation during psoriasis and skin wounds (Elfatoiki et al, 2016; Lacey et al, 2016; Totté et al, 2016). Both bacteria are able to form biofilms inside the niches that they colonize (Daum, 2007; Jahns et al, 2012; Jahns and Alexeyev, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The age group varying from 24 and 34 years is the most represented in our study. However in Martin and all set in France, the most represented age group is 20 to 25 years [3].…”
Section: Socio Demographic Charactersmentioning
confidence: 97%
“…As for amenorrheait happens in about 2 to 3% of cases of use. In the other cases, genital infection and organic lesion must previously be looked for before thinking of the atrophy of the endometrium, and possibly the temporary prescription of a pill with more dose of estrogen, or even a light dose of estrogen during a short period [3].…”
Section: Metrorrhagia and Amenorrheamentioning
confidence: 99%